Chapter 4

You might also like

Download as pdf or txt
Download as pdf or txt
You are on page 1of 9

CHAPTER 4

METHODS OF PROOFS

4.1 Direct Proof


Let P and Q be statements and consider the statement P ⇒ Q. The construction
of the direct proof of the implication P ⇒ Q involves the figuration of statements
R1 , R2 ,..., Rn , construction and arrangement of the implications

P ⇒ R1 , R1 ⇒ R2 , ..., Rn−1 ⇒ Rn , Rn ⇒ Q

By the Law of Syllogism, if all the above implications are true, then P ⇒ Q is true.

Note that the construction of a direct proof is not easy, it may involve
observation, intuition, practice, skill, patience, effort, experience, etc.
Sometimes it requires LUCK.

Summary of the Method:

Prove: P ⇒ Q
Proof : Let P . Then R1 . Thus, R2 . Hence, R3 . Therefore, Q. 

In the above summary, we have the arrangements of implications

P ⇒ R1 , R1 ⇒ R2 , R2 ⇒ R3 , R3 ⇒ Q

By the Law of Syllogism, if all the above implications are true, then P ⇒ Q is true.

Let us consider basic definitions which are very familiar. We will apply these
definitions to some of the examples.

A definition is a double implication statement but it is usually written in an


implication form. Since a definition is a double implication, it consists of four
implication statements.

Definition 4.1.1 Let a, b ∈ R. Then a > b if a − b is positive.

Restatement : Let a, b ∈ R. Then a > b if and only if a − b is positive.

Below are the four implication statements of Definition 4.1.1:

(1) Let a, b ∈ R. If a > b, then a − b is positive.


(2) Let a, b ∈ R. If a − b is positive, then a > b.
(3) Let a, b ∈ R. If a 6> b, then a − b is not positive.
(4) Let a, b ∈ R. If a − b is not positive, then a 6> b.

1
Theorem 4.1.2 Let a, b, c, d ∈ R.
1. If a > b and b > c, then a > c.
2. If a > b, then a + c > b + c.
3. If a > b and c > d, then a + c > b + d.
4. If a > b and c is positive, then ac > bc.
5. If a > b and c is negative, then bc > ac.

Let us now prove some of these properties using Definition 4.1.1.

In the first example, we apply the property: the sum of two positive real numbers
is positive.

Example 4.1.3 Let a, b, c ∈ R. Prove that if a > b and b > c, then a > c.

Proof : Let a > b and b > c. Then a − b is positive and b − c is positive. Thus,
(a − b) + (b − c) is positive. Hence, a − c is positive. Therefore, a > c. 

In the next example, we apply the trick: a − b = a + 0 − b = a + (c − c) − b =


(a + c) − (b + c).

Example 4.1.4 Let a, b, c ∈ R. Prove that if a > b, then a + c > b + c.

Proof : Let a > b. Then a − b is positive. Thus, a + c − c − b is positive. Hence,


(a + c) − (b + c) is positive. Therefore, a + c > b + c. 

The next example is similar to Example 4.1.3. Take note the following:
(a − b) + (c − d) = a − b + c − d = a + c − b − d = (a + c) − (b + d).

Example 4.1.5 Let a, b, c ∈ R. Prove that if a > b and c > d, then a + c > b + d.

Proof : Let a > b and c > d. Then a − b and c − d are positive. Thus, (a − b) + (c − d)
is positive. Hence, (a + c) − (b + d) is positive. Therefore, a + c > b + d. 

In the next example, apply the property: the product of two positive real numbers
is positive.

Example 4.1.6 Let a, b, c ∈ R. Prove that if a > b and c is positive, then ac > bc.

Proof : Let a > b and c is positive. Then a − b is positive and c is positive. Thus,
(a − b)c is positive. Hence, ac − bc is positive. Therefore, ac > bc. 

Example 4.1.7 Let a, b, c ∈ R. Prove that if a > b and c is negative, then bc > ac.

2
Proof : Let a > b and c is negative. Then a − b is positive and −c is positive. Thus,
(a − b)(−c) is positive. Hence, bc − ac is positive. Therefore, bc > ac. 

Definition 4.1.8 Let m be an integer. Then m is even if there exists an integer k


such that m = 2k.
Restatement: Let m be an integer. Then m is even if and only if ∃ k ∈ Z such
that m = 2k.

Definition 4.1.9 Let n be an integer. Then n is odd if there exists an integer t such
that n = 2t + 1.
Restatement: Let n be an integer. Then n is odd if and only if ∃ t ∈ Z such that
n = 2t + 1.

Example 4.1.10 Prove: If m is an even integer, then m2 + 2 is an even integer.

Proof : Let m be an even integer. Then ∃ k ∈ Z such that m = 2k. Thus,


m2 + 2 = (2k)2 + 2 = 4k 2 + 2 = 2(2k 2 + 1).
Let p = 2k 2 + 1 ∈ Z. Hence, ∃ p ∈ Z such that m2 + 2 = 2p. Therefore, m2 + 2 is
even. 

Example 4.1.11 Prove: If n is an odd integer, then n2 + 3 is even.

Proof : Let n be an odd integer. Then ∃ t ∈ Z such that n = 2t + 1. Thus,


n2 + 3 = (2t + 1)2 + 3 = 4t2 + 4t + 1 + 3 = 4t2 + 4t + 4 = 2(2t2 + 2t + 2).
Let p = 2t2 + 2t + 2 ∈ Z. Hence, ∃ p ∈ Z such that n2 + 3 = 2p. Therefore, n2 + 3 is
even. 

Example 4.1.12 Prove: If n is an odd integer, then n3 + −2n is odd.

Proof : Let n be an odd integer. Then ∃ t ∈ Z such that n = 2t + 1. Thus,


n3 − 2n = (2t + 1)3 − 2(2t + 1)
= 8t3 + 12t2 + 6t + 1 − 4t − 2
= 8t3 + 12t2 + 2t − 1
= 8t3 + 12t2 + 2t − 2 + 1
= 2(4t3 + 6t2 + t − 1) + 1.
Let p = 4t3 + 6t2 + t − 1 ∈ Z. Hence, ∃ p ∈ Z such that n3 − 2n = 2p + 1. Therefore,
n3 − 2n is odd. 

Example 4.1.13 Let m, n ∈ Z. Prove that if m is even and n is odd, then mn + 3


is odd.

Proof : Let m be even and n be odd. Then ∃ k ∈ Z such that m = 2k and ∃ t ∈ Z


such that n = 2t + 1. Thus,

3
mn + 3 = (2k)(2t + 1) + 3 = 4kt + 2k + +3 = 4kt + 2k + 2 + 1 = 2(2kt + k + 1) + 1.

Let p = 2kt + k + 1 ∈ Z. Hence, ∃ p ∈ Z such that mn + 3 = 2p + 1. Therefore,


mn + 3 is odd. 

Example 4.1.14 Let m, n ∈ Z. Prove that if m is even and n is odd, then


m2 + mn + n2 is odd.

Proof : Let m be even and n be odd. Then ∃ k, t ∈ Z such that m = 2k and n = 2t+1.
Thus,

m2 + mn + n2 = (2k)2 + (2k)(2t + 1) + (2t + 1)2


= 4k 2 + 4kt + 2k + 4t2 + 4t + 1
= 2(2k 2 + 2kt + k + 2t2 + 2t) + 1.

Let p = 2k 2 + 2kt + k + 2t2 + 2t ∈ Z. Hence, ∃ p ∈ Z such that m2 + mn + n2 = 2p + 1.


Therefore, m2 + mn + n2 is odd. 

4.2 Indirect Proof


There are two types of indirect proofs, the proof by contradiction and the
contrapositive proof. The most important part of these proofs is the assumption
that the comclusion Q is false or the statement ∼ Q is true.

Proof by Contradiction

This method of proof apply the following technique. If R is a contradiction


statement, then the two statements

(P ∧ ∼ Q) ⇒ R and P ⇒ Q

are logically equivalent. Hence, to prove that P ⇒ Q, we show that (P ∧ ∼ Q)


implies a contradiction.

Summary of the Method:

Prove: P ⇒ Q
Proof : Let P . Suppose ∼ Q. Then R1 . Thus, R2 ... Hence, Rn . This is a
contradiction to... Therefore, Q. 

Theorem 4.2.1 Let a ∈ R.


1. If a > 0, then a1 > 0.
2. If a < 0, then a1 < 0.

1
Example 4.2.2 Let a ∈ R. Prove that if a > 0, then a
> 0.

4
Proof : Let a > 0. Suppose that a1 ≯ 0. Then a1 ≤ 0. Thus, a( a1 ) ≤ a(0). Hence,
1 ≤ 0. This is a contradiction to the fact that 1 > 0. Therefore, a1 > 0. 

1
Example 4.2.3 Let a ∈ R. Prove that if a < 0, then a
< 0.

Proof : Let a < 0. Suppose that a1 ≮ 0. Then a1 ≥ 0. Thus, a( a1 ) ≤ a(0). Hence,


1 ≤ 0. This is a contradiction to the fact that 1 > 0. Therefore, a1 < 0. 
1
Note that in the above proof: since a < 0 and a
≥ 0, applying Theorem 4.1.2(5),
we get a( a1 ) ≤ a(0).

Definition 4.2.4 Let X and Y be sets. Then X ⊆ Y if ∀ x ∈ X, x ∈ Y .

Example 4.2.5 Prove that the empty set is a subset of every set.

Restatement: If A is any set, then ∅ ⊆ A.

Proof : Let A be any set. Suppose that ∅ * A. Then ∃ x ∈ ∅ such that x ∈


/ A. This
contradicts the fact that ∅ has no element. Therefore, ∅ ⊆ A. 

Theorem 4.2.6 (Trichotomy Property) If a ∈ R, then exactly one of the following


holds:

a > 0, a = 0, a < 0.

Example 4.2.7 Let a, b ∈ R. Use the Trichotomy Property to prove that if a ≤ b


and a ≥ b, then a = b.

Proof : Let a ≤ b and a ≥ b. Suppose that a 6= b. Then a − b 6= 0. By the Trichotomy


Property, a − b > 0 or a − b < 0. Hence, a > b or a < b. This contradicts the
hypothesis. Therefore, a = b. 

Theorem 4.2.8 Let a ∈ R. If a 6= 0, then a2 > 0.

Example 4.2.9 Let a, b ∈ R. Prove that if a2 + b2 = 0, then a = 0 and b = 0.

Proof : Let a2 + b2 = 0. Suppose that a 6= 0 or b 6= 0. By Theorem 4.2.8, a2 > 0 or


b2 > 0. Hence, a2 + b2 > 0. This contradicts the hypothesis. Therefore, a = 0 and
b = 0. 

5
Contrapositive Proof

Summary of the Method:

Prove: P ⇒ Q
Proof (Contrapositive): Let ∼ Q. Then R1 . Thus, R2 ... Hence, Rn . Therefore, ∼ P .


To prove the statement P ⇒ Q using the contapositive proof is to prove its


contrapositive ∼ Q ⇒∼ P . Thus, it is important to know the contrapositive of an
implication statement.

Example 4.2.10 Let a, b ∈ R. Use the Trichotomy Property to prove that if a ≤ b


and a ≥ b, then a = b.

Proof (Contrapositive): Let a 6= b. Then a − b 6= 0. By the Trichotomy Property,


a − b > 0 or a − b < 0. Hence, a > b or a < b. 

Note that the contrapositive of the statement to prove is ”Let a, b ∈ R. If a 6= b,


then a > b or a < b”.

Example 4.2.11 Let a, b ∈ R. Prove that if a2 + b2 = 0, then a = 0 and b = 0.

Proof (Contrapositive): Let a 6= 0 or b 6= 0. By Theorem 4.2.8, a2 > 0 or b2 > 0.


Thus, a2 + b2 > 0. Hence, a2 + b2 6= 0. 

Note that the contrapositive of the statement to prove is ”Let a, b ∈ R. If a 6= 0


or b 6= 0, then a2 + b2 6= 0”.

4.3 Mathematical Induction


Theorem 4.3.1 (Principle of Well-Ordering) Every nonempty subset of the set
of positive integers has a smallest elemant, that is, if S ⊆ Z+ and S 6= ∅, then there
exists x0 ∈ S such that x0 ≤ x for all x ∈ S.

Theorem 4.3.2 (Principle of Mathematical Induction) Let S be a subset of N


that possesses the properties:
(1) 1 ∈ S;
(2) if k ∈ S, then k + 1 ∈ S.
Then S = N.

Theorem 4.3.3 (Principle of Mathematical Induction, Version 2) For each


n ∈ N, let P (n) be a statement about n. Suppose that:
(1) P (1) is true;
(2) if P (k) is true, then P (k + 1) is true.
Then P (n) is true for all n ∈ N.

6
n(n + 1)
Example 4.3.4 Prove: ∀ n ∈ N, 1 + 2 + 3 + ... + n = .
2
n(n + 1)
Proof : Let P (n) be 1 + 2 + 3 + ... + n = .
2
1(1 + 1)
(1) Let n = 1. Then 1 = . Thus, 1 = 1. Hence, P (1) is true.
2
k(k + 1)
(2) Let P (k) be true. Then 1 + 2 + 3 + ... + k = . Thus,
2
k(k + 1)
1 + 2 + 3 + ... + k + (k + 1) = + (k + 1)
2
k(k + 1) + 2(k + 1)
=
2
(k + 1)(k + 2)
= .
2
Hence, P (k + 1) is true.

n(n + 1)
Therefore, ∀ n ∈ N, 1 + 2 + 3 + ... + n = .
2

1 − rn+1
Example 4.3.5 Let r ∈ R, r 6= 1. Prove: ∀ n ∈ N, 1 + r + r2 + ... + rn = .
1−r
1 − rn+1
Proof : Let P (n) be 1 + r + r2 + ... + rn = .
1−r
1 − r1+1
(1) Let n = 1. Then 1 + r = . Thus, 1 + r = 1 + r. Hence, P (1) is true.
1−r
1 − rk+1
(2) Let P (k) be true. Then 1 + r + r2 + ... + rk = . Thus,
1−r
1 − rk+1
1 + r + r2 + ... + rk + rk+1 = + rk+1
1−r
1 − rk+1 + rk+1 − rk+2
=
1−r
1 − rk+2
= .
1−r
Hence, P (k + 1) is true.

1 − rn+1
Therefore, ∀ n ∈ N, 1 + r + r2 + ... + rn = .
1−r

Example 4.3.6 Prove: ∀ n ∈ N, n < 2n .

Proof : Let P (n) be n < 2n .

(1) Let n = 1. Then 1 < 21 . Hence, P (1) is true.

7
(2) Let P (k) be true. Then k < 2k . Thus,

k + 1 < 2k + 1
< 2k + 2k , (1 < 2k )
= 2k · 2
= 2k+1 .

Hence, P (k + 1) is true.

Therefore, ∀ n ∈ N, n < 2n . 

Example 4.3.7 Prove: ∀ n ≥ 4, n ∈ N, 2n < n!.

Proof : Let P (n) be 2n < n!.

(1) Let n = 4. Then 24 < 4!. Thus, 16 < 24. Hence, P (4) is true.

(2) ∀k ≥ 4, let P (k) be true. Then 2k < k!. Thus,

2k+1 = 2k + 2k
< k! + k!
< k · k! + k!
= (k + 1)k!
= (k + 1)!.

Hence, P (k + 1) is true.

Therefore, ∀ n ≥ 4, n ∈ N, 2n < n!. 

Example 4.3.8 Prove: ∀ n ∈ N, 9n − 1 is divisible by 8.

Proof : Let P (n) be 9n − 1 is divisible by 8.

(1) Let n = 1. Then 91 − 1 = 8 is divisible by 8. Hence, P (1) is true.

(2) Let P (k) be true. Then 9k − 1 is divisible by 8. Thus,

9k+1 − 1 = 9 · 9k − 9k + 9k − 1
= 8 · 9k + (9k − 1).

Since 8 · 9k and 9k − 1 are divisible by 8, it follows that 8 · 9k + (9k − 1) is divisible


by 8. Thus, 9k+1 − 1 is divisible by 8. Hence, P (k + 1) is true.

Therefore, ∀ n ∈ N, 9n − 1 is divisible by 8. 

8
Exercises

I. Prove the following statements.


1. If m is an even integer, then 3m + 1 is odd.
2. If n is an odd integer, then (n + 1)2 is even.
3. If m is an even integer, then n3 + n + 4 is even.
4. Let m and n be integers. If m is even and n is odd, then (m + n)2 is odd.
5. Let m and n be integers. If m is even and n is odd, then m2 + n2 + 3 is even.

II. Prove the following statements.


1. Let a, b ∈ R. Then a2 + b2 = 0 if and√only if a = 0 and b = 0.
2. Let a, b ∈ R. If 0 < a < b, then a < ab < b and 0 < 1b < a1 .
3. Let a, b, c, d ∈ R. If 0 < a < b and 0 < c < d, then 0 < ac < bd.
4. Let a, b, c, d ∈ R. If a < b and c < d, then ad + bc < ac + bd.
5. Let c ∈ R. If 0 < c < 1, then 0 < c2 < c < 1.

III. Prove the following statements by Mathematical Induction.


n
1. ∀ n ∈ N, 1 + 3 + 32 + 33 + ... + 3n−1 = 3 2−1 .
2 2
2. ∀ n ∈ N, 13 + 23 + 33 + ... + n3 = n (n+1)
4
.
3n(n+1)
3. ∀ n ∈ N, 3 + 6 + 9 + ... + 3n = 2
.
2
4. ∀ n ∈ N, n + 3n is divisible by 2.
5. ∀ n ∈ N, 52n − 1 is divisible by 8.
6. ∀ n ∈ N, 3 is a factor of n2 − n.
7. ∀ n ≥ 7, n ∈ N, 3n < n!.
8. ∀ n ≥ 5, n ∈ N, 2n − 3 < 2n−2 .
9. ∀ n ≥ 5, n ∈ N, n2 < 2n .
10. ∀ n ∈ N, n2 ≥ n.

You might also like